Poverty Alleviation Model of “Laut” Tribe and Structure of Economy in Indragiri Hilir Regency, Riau Province - Hidir, Achmad; Jonyanis, Jonyanis (International Journal of Economic, Business & Applications, 2017)
The life of fisherman is always synonymous with poverty. There are many causes of poverty in the life of fisherman, such as, the lack of access to capital sources, access to technology, access to market and low participation of the community in the management of natural resources. Social stratification and capital penetration among fishermen also cause poverty and conflict potential among them becomes more complicated. This study analyses interrelation pattern among fishermen in the context of social stratification and identifies adaptation strategies of traditional fishermen in dealing with problem of fish catching and surviving in the middle of environmental change in their region. The objective of this study is to formulate the right pattern to eliminate conflict potential among level of fishermen and to recommend the right poverty alleviation model to develop in their region.This study uses mixing method approach by combining descriptive quantitative approach and qualitative approach as well as participatory approach. The target of this study is “laut” tribe fishermen in Panglima Raja village (Concong luar), community figures, village government officer and sub district government officer in Indragiri Hilir regency. Collected data will be analyzed with interactive analysis model.Research result shows that the low selling value and catching result of fishermen are caused by the limit of technology and high cost fare that make traditional fishermen are still struggling with poverty. The low human resources quality of traditional fishermen has implication to all sides of fishermen’s life especially adaptation ability to the changes in aquatic ecosystems. Therefore, the efforts of community empowerment through education actualization, allignments on marginal fishermen communities and government commitment need to get attention.